Adrenomedullin Expression Is Associated With the Severity and Poor Prognosis of Interstitial Lung Disease in Dermatomyositis Patients - Ye, Lifang; Zuo, Yu; Chen, Fang; Xu, Yuetong; Zhang, Puli; Yang, Hongxia; Peng, Qinglin; Wang, Guochun; Shu, Xiaoming (Frontiers in Immunology, 2022)
Objective To evaluate adrenomedullin mRNA levels in the peripheral blood mononuclear cells (PBMCs) of patients with dermatomyositis (DM) as well as their correlation with the severity of interstitial lung disease (ILD). Methods A total of 41 DM patients and seven immune-mediated necrotizing myopathy (IMNM) patients were recruited, in addition to 21 healthy controls (HCs). The adrenomedullin mRNA levels in PBMCs were measured via quantitative reverse-transcription real-time polymerase chain reaction (qRT-PCR). The associations between adrenomedullin expression levels and major clinical, laboratory, pulmonary function parameters and the prognosis of patients with DM-related ILD (DM-ILD) were analyzed. Immunohistochemical analysis was performed on lung tissues of DM-ILD patients to determine adrenomedullin expression. Results Adrenomedullin mRNA levels in PBMCs were significantly higher in DM patients than in IMNM patients and HCs (p = 0.022 and p<0.001, respectively). Among DM patients, the levels were significantly higher in those with rapidly progressive ILD (RP-ILD) than in those with chronic ILD (p = 0.002) or without ILD (p < 0.001). The adrenomedullin mRNA levels in DM-ILD were positively correlated with serum ferritin (r =0.507, p =0.002), lactate dehydrogenase (LDH) (r =0.350, p =0.045), and lung visual analog scale (VAS) (r=0.392, p=0.021) and were negatively correlated with pulmonary function test parameters, including predicted forced vital capacity (FVC)% (r = −0.523, p = 0.025), forced expiratory volume in 1 s (FEV1)% (r = -0.539, p = 0.020), and diffusing capacity of carbon monoxide (DLco)% (r = -0.495, p = 0.036). Immunohistochemical analysis of adrenomedullin confirmed higher expression in the alveolar epithelial cells and macrophages of DM patients with RP-ILD. Among the DM patients with ILD, the six decedents exhibited higher adrenomedullin levels than the 28 survivors (p = 0.042). The cumulative survival rate was significantly lower (62.5% vs. 100%, P = 0.005) in patients with an adrenomedullin level > 0.053 than in those with a level <0.053. Conclusions Adrenomedullin levels are upregulated in DM patients with RP-ILD and are associated with ILD severity and poor prognosis. Adrenomedullin may be a potential prognostic biomarker in DM patients with ILD, although need further investigation.